PREVENTION TOOLS IN THE AREA OF THE KNEE COMPLEX - TREATMENT AND PROPHYLAXIS - Yani Shivachev; Stanislava Bogomilova (Peytchinski Publishing, 2020)
Injuries to the knee complex are one of the most common. In the world, physical therapeutic programs are being applied, adapted to the adequate recovery of patients, including athletes with such pathology. There are well-established physical therapeutic methodologies in accordance with the rehabilitation potential and the needs of the athletes, as in some of the cases of incorrect rehabilitation or their early return to sports activity, recurrences happen. This imposes the development of prevention strategies involving multidisciplinary teams between which there is a systematical exchange of information about the athlete's condition in order to prevent soft tissue damage or to reduce the risk of relapses. In this team, a key unit in the preparation of the preventive program for optimal fitness, performance and reduction of the risk of soft tissue injuries, is the physical therapist who is the main member of the multidisciplinary team. The aim of this article is to present the most common physical therapeutic means for the prevention of injuries in the area of ​​the knee complex.